Neutrophils Require Activation to Express Functional Cell-Surface Complement Receptor Immunoglobulin - Small, Annabelle G.; Perveen, Khalida; Putty, Trishni; Patel, Nikita; Quinn, Patrick; Wechalekar, Mihir D.; Hii, Charles S.; Quach, Alex; Ferrante, Antonio (Frontiers in Immunology, 2022)
The phagocytosis-promoting complement receptor, Complement Receptor Immunoglobulin (CRIg), is exclusively expressed on macrophages. It has been demonstrated that expression in macrophages could be modulated by inflammatory mediators, including cytokines. This raised the possibility that a major phagocyte, the neutrophil, may also express CRIg following activation with inflammatory mediators. Here we show that peripheral blood neutrophil lysates subjected to protein analysis by Western blot revealed a 35 kDa CRIg isoform. This was consistent with the expression of CRIg mRNA by RT-PCR. By flow cytometry, CRIg was detected intracellularly and in very minor amounts on the cell surface. Interestingly, expression on the cell surface was significantly increased to functional levels after activation with inflammatory mediators/neutrophil activators; N-Formylmethionine-leucyl-phenylalanine, tumor necrosis factor, bacterial lipopolysaccharide, leukotriene B4 and phorbol myristate acetate. The increase in expression required p38 MAP kinase and protein kinase C activation, as well as intracellular calcium. Neutrophils which were defective in actin microfilament reorganization due to a mutation in ARPC1B or inhibition of its upstream regulator, Rac2 lose their ability to upregulate CRIg expression. Inhibition of another small GTPase, Rab27a, with pharmacological inhibitors prevents the increase in CRIg expression, suggesting a requirement for the actin cytoskeleton and exocytosis. Engagement of CRIg on TNF-primed neutrophils with an anti-CRIg monoclonal antibody increased the release of superoxide and promoted the activation of p38 but not ERK1/ERK2 or JNK. The data demonstrate that neutrophils express CRIg which is upregulated by inflammatory mediators, increasing our understanding and importance of CRIg in innate immunity and inflammation.